Stone Fruits: Growth and Nitrogen and Organic Acid Metabolism in the Fruits and Seeds—A Review - Famiani, Franco; Bonghi, Claudio; Chen, Zhi-Hui; Drincovich, María F.; Farinelli, Daniela; Lara, María V.; Proietti, Simona; Rosati, Adolfo; Vizzotto, Giannina; Walker, Robert P. (Frontiers in Plant Science, 2020)
Stone fruits of the Rosaceae family consist of several distinct parts, and these include the flesh, woody endocarp and seed. To understand the metabolism of these fruits it is necessary to have a knowledge of both their structure and growth characteristics. The nitrogen metabolism of the different tissues of stone fruits is interlinked. For example, there is an import and storage of nitrogenous compounds in the endocarp that then are exported in the seed. Moreover, there are links between the metabolism of nitrogen and that of malic and citric acids. In this article, the structure and growth characteristics, together with the import/export, contents, metabolism and functions of nitrogenous compounds and organic acids in the different part of stone fruits and their seeds are reviewed.